EKSPLORASI IMPLEMENTASI REFORMASI PERPAJAKAN DI KANTOR PELAYANAN PAJAK - Susanto, Dian Agung (Unitri Press, 2021)
This study aims to explore the implementation of tax reform, especially in the service sector at the Tax Service Office. This study was using a descriptive method that uses a qualitative study approach with a research setting at the Denpasar Middle Tax Service Office. The researcher as the key instrument collected the data himself through documentation and interviews with informants. The results of this study was to indicate that tax reform, especially in the service sector, provides a positive implementation of tax revenue and taxpayer compliance. The availability and validity of the data filled in by the Taxpayer makes it easier for the DGT to supervise the Taxpayer, in addition to simplifying the reporting of SPT, the ease of reporting through an online basis, and convenient facilities that can increase the voluntary compliance of the taxpayer.